2018
DOI: 10.1002/anie.201811873
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation Behavior of a Six‐Membered Cyclic Frustrated Phosphane/Borane Lewis Pair: Formation of a Supramolecular Cyclooctameric Macrocyclic Ring System

Abstract: A new six‐membered cyclic frustrated phosphane/borane Lewis pair was liberated from its HB(C6F5)2 adduct by treatment with vinylcyclohexane. The system is an active frustrated Lewis pair that undergoes cycloaddition reactions with suitable π reagents and it splits dihydrogen. At room temperature in solution the new compound is a monomer, however, in the crystal and in solution at low temperature it aggregates to a thermodynamically favoured supramolecular macrocyclic cyclooctamer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
19
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 46 publications
0
19
0
2
Order By: Relevance
“…metathesis followed by removal of the coordinatedH B-borane by as ubsequent hydroborations tep. [9] This was in an equilibrium with an associated macrocyclic supramolecular cyclooctameric structure, which was favored in the crystal and at low temperature in solution. We have now found that the monomeric cyclic six-membered P/B structure 6 serves as ar eactive component in av ariety of cycloaddition reactions, among them with carbon dioxide.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…metathesis followed by removal of the coordinatedH B-borane by as ubsequent hydroborations tep. [9] This was in an equilibrium with an associated macrocyclic supramolecular cyclooctameric structure, which was favored in the crystal and at low temperature in solution. We have now found that the monomeric cyclic six-membered P/B structure 6 serves as ar eactive component in av ariety of cycloaddition reactions, among them with carbon dioxide.…”
mentioning
confidence: 99%
“…[18] We note that cyclo-P/B FLPs often show at endency for aggregation. [6,9] In view of these observations it seems that the emerging chemistry of the cyclo-P/B FLP systems might lead to the Scheme4.Rearrangement of 6 and trapping with ac onjugated diene. disclosure of as upramolecular structuralF LP chemistry, [19] which mayp otentially lead to new FLP reactivities.…”
mentioning
confidence: 99%
“…Aview of the cyclooctameric ring structure (7) 8 (thermal ellipsoids are shown at 15 %p robability). [17] Hydrogen atoms are omitted and only the connecting carbon atoms of the bulky C 6 , and determined their free-energy content relative to that of the monomer 7.T he cyclooctamer (7) 8 was the only cyclic supramolecular structure that we could locate as am inimum structure on this hypersurface.W efound no other macrocyclic supra-structure of significant stability,b ut there were several open-chain structures that represented thermally accessible local minima (Figure 3). According to our DFT analysis,the monomer 7 is the energetically favored structure in CH 2 Cl 2 solution at 298 K. Theo ligomers fall in as mall free-energy window of about 2kcal mol À1 and thus,lowering the temperature leads to increasingly favouring the aggregated structure.T his aggregation is attributed to ad ecrease of the entropic penalty for cyclic aggregation.…”
mentioning
confidence: 99%
“…The Dd 19 F m,p chemical shift difference in 11 is 2.7 ppm. [17] Angewandte Chemie Communications TheP /B FLP 7 is an active dihydrogen splitting agent. [1] Heterolytic H À Hc leavage was achieved by exposure of 7 to dihydrogen in CH 2 Cl 2 solution (2 bar H 2 ,R T, 5d)a nd we isolated the zwitterionic phosphonium/hydridoborate product 12 as awhite solid in 74 %yield (Scheme 3).…”
mentioning
confidence: 99%
See 1 more Smart Citation